2014
DOI: 10.1039/c4ra03398a
|View full text |Cite
|
Sign up to set email alerts
|

Strontium pyrophosphate modified by phosphoric acid for the dehydration of lactic acid to acrylic acid

Abstract: The dehydration of lactic acid to acrylic acid over strontium catalysts was investigated. Strontium catalysts were prepared by a precipitation method. The catalysts were calcined at 500 C for 6 hours in an air atmosphere and characterized by SEM for morphological features, by XRD for crystal phases, by FTIR for structure, by N 2 sorption for specific surface area, and by the Hammett indicator method for acidity. As for bare strontium catalysts, the types of anions have significant effects on the activity due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 35 publications
(33 reference statements)
3
48
0
Order By: Relevance
“…Lewis acid sites are known to be able to catalyze dehydration reactions. [20][21][22][23][24][25][26][27][28]41 Moreover, Na + in NaY has been shown 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 25 to be active in the dehyration of IPA, which is a useful surrogate molecule for ML because both have a secondary hydroxyl group and IPA cannot generate Brønsted acid sites on NaY via ionexchange. 41 To further explore the hypothesis that Lewis acid sites are the active sites for ML dehydration, IPA dehydration is used as a model reaction.…”
Section: Additionally Although the Combination Band Is Observed Whenmentioning
confidence: 99%
“…Lewis acid sites are known to be able to catalyze dehydration reactions. [20][21][22][23][24][25][26][27][28]41 Moreover, Na + in NaY has been shown 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 25 to be active in the dehyration of IPA, which is a useful surrogate molecule for ML because both have a secondary hydroxyl group and IPA cannot generate Brønsted acid sites on NaY via ionexchange. 41 To further explore the hypothesis that Lewis acid sites are the active sites for ML dehydration, IPA dehydration is used as a model reaction.…”
Section: Additionally Although the Combination Band Is Observed Whenmentioning
confidence: 99%
“…[1][2][3][4] Its production mainly relies on the oxidization of propanal obtained from ethylene via hydroformylation. Lactic acid (LA) as sustainable feedstock is widely used to synthesize various chemicals such as acrylic acid, [19][20][21][22][23][24] acetaldehyde, 25-27 2,3pentanedione 28,29 and polylactic acid. However theses processes for propionic acid production are mostly based on raw materials derived from petroleum, which will become scarcer and more expensive with the rapid development of chemical industries in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…41 The reaction mechanism was thought to contain two steps: (1) dehydration of LA into acrylic acid; and (2) hydrogenation of acrylic acid into propionic acid. Among these solid catalysts are sulfates, 42,43 phosphates, 22,23,28,29 alkali or alkali earth metal-modied zeolites, 19,44 mesoporous carbon, 45 metal oxides, 25,26,46 and supported platinum. Korstanje et al 4 subsequently reported that non-noble metal complexes based on molybdenum were also used to catalyze the deoxygenation of LA into propionic acid, achieving 41% yield of sodium propionate.…”
Section: Introductionmentioning
confidence: 99%
“…(4) and (5 [18,[52][53][54]. In this section, effect of preparation parameters such as pH values, calcination temperatures and Mg/Al molar ratios on the specific surface, pore volume and pore distribution of the catalysts was investigated with nitrogen adsorption-desorption at 77 K using Autosorb IQ instrument, and the results were depicted in Tables 1-3 and Figs.…”
Section: Catalyst Evaluationmentioning
confidence: 99%
“…LHSV is generally used to evaluate the performance of heterogeneous catalyst [53,57,58]. Table 9 shows the influence of LA LHSV on reaction performance.…”
Section: Liquid Hourly Space Velocity (Lhsv)mentioning
confidence: 99%